2014
DOI: 10.1521/bumc.2014.78.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about e-cigarette safety may lead to e-smoking during pregnancy

Abstract: Electronic cigarettes (e-cigarettes) are nicotine-delivery devices that are increasingly used, especially by young people. Because e-cigarettes lack many of the substances found in regular tobacco, they are often perceived as a safer smoking alternative, especially in high-risk situations such as pregnancy. However, studies suggest that it is exposure to nicotine that is most detrimental to prenatal development. The authors studied perceptions of tobacco and e-cigarette health risks using a multiple-choice sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 16 publications
2
76
0
2
Order By: Relevance
“…We found women were concerned about the health and safety effects of using e-cigarettes during pregnancy. However survey data suggests pregnant women view e-cigarettes as less harmful than smoking 24 , which is similar to the views reported by some young adults 25 and obstetrician-gynaecologists 26 .…”
Section: Discussionsupporting
confidence: 75%
“…We found women were concerned about the health and safety effects of using e-cigarettes during pregnancy. However survey data suggests pregnant women view e-cigarettes as less harmful than smoking 24 , which is similar to the views reported by some young adults 25 and obstetrician-gynaecologists 26 .…”
Section: Discussionsupporting
confidence: 75%
“…For example, some have suggested that perceptions of e-cigarette safety may inadvertently expose developing fetuses to nicotine, the substance primarily linked to adverse fetal effects. 23 In light of the potential widespread implications of harm perceptions, we sought to provide an updated analysis on youth perceptions of relative harm and addictiveness of multiple noncigarette tobacco products, including a novel analysis of how such perceptions may have changed over time. By using data from the 2014 National Youth Tobacco Survey (NYTS), we provide nationally representative estimates of the perceived relative harm and addictiveness of e-cigarettes, cigars, and smokeless tobacco compared with traditional cigarettes and, in so doing, examine demographic and tobacco use correlates of those perceptions.…”
mentioning
confidence: 99%
“…A termék ártalomcsökkentő szerepét hangsúlyozó intenzív reklámozás miatt a várandósok körében is egyre elterjedtebb az a nézet, hogy az e-cigaretta használata biztonságos alternatívája lehet a dohányzásnak [48]. Tekintettel a nikotin által a magzatra és a terhességre gyakorolt ismert káros hatásokra, különösen nyugtalanító, hogy megfelelő prevenciós tevékenység (felvilágosítás a káros hatásokról, leszokástámogatási lehetőségekről) hiányában növekvő arányban választhatják dohányzó vá-randós nők is az e-cigarettát [49].…”
Section: Az E-cigaretta Terjedésének Népegészségügyi Szempontjaiunclassified
“…A termék ártalomcsökkentő szerepét hangsúlyozó intenzív reklámozás miatt a várandósok körében is egyre elterjedtebb az a nézet, hogy az e-cigaretta használata biztonságos alternatívája lehet a dohányzásnak [48]. Tekintettel a nikotin által a magzatra és a terhességre gyakorolt ismert káros hatásokra, különösen nyugtalanító, hogy megfelelő prevenciós tevékenység (felvilágosítás a káros hatásokról, leszokástámogatási lehetőségekről) hiányában növekvő arányban választhatják dohányzó vá-randós nők is az e-cigarettát [49].A dohányzás visszaszorítására és a leszokás támogatá-sára hozott intézkedések hatékonysága érdekében kívá-natos, hogy az e-cigarettára ugyanazok a szabályok vonatkozzanak, mint a hagyományos dohánytermékekre, azaz a dohányzást tiltó helyeken ne lehessen e-cigarettát sem használni, tilos legyen a termék reklámozása, illetve az ízesítő aromák használata [3]. Az amerikai szövetségi államok több mint fele korlátozza az e-cigaretta haszná-latát, és ennek érdekében a következő szabályozásokat vezette be: életkorhoz kötötte a dohánytermékekhez, így az amerikai szabályozás szerint annak minősülő e-cigarettához való hozzáférést, a füstmentes levegőt előíró törvények korlátozzák, hogy hol lehet "rágyújtani", illetve jövedéki adót vetnek ki a különböző dohánytermé-kekre, így az e-cigarettára is [50].…”
unclassified